Investigating The Effects Of Demographic Variables On The Role Of Media Educations Of Iran Helal Institute In Increasing Public Awareness For Rehabilitation After Earthquake In The Possible Earthquake In Tehran - Filom, Zahra (The Turkish Online Journal of Design Art and Communication, 2016)
The aim of this study was to investigating the effects of demographic variables on the role of media educations of Iran Helal institute in increasing public awareness for rehabilitation after earthquake in the possible earthquake in Tehran. In the quantitative research, using survey method and questionnaire tool, investigating the role of educational media of Helal institute on public awareness for rehabilitation after earthquake. The study population included all persons 15-65 years at the time of implementation of project were living in 5 regions in North, South, East, West and center of Tehran. Sample size n=380 in each region is calculated based on Cochran formula. Overall, this study shows that media educations of Helal institute on people's awareness about prevention and preparing and informing the public about the rehabilitation after the earthquake is effective.
Keywords: media educations; Iran Helal Institute; public awareness; possible earthquake in Tehran; Medya eğitimler; İran Helal Enstitüsü; halkın bilinçlendirilmesi; Tahran'da olası deprem